Pembelajaran Bahasa Inggris Dan Pemberian Sembako Kepada Anak-Anak di Panti Asuhan Naungan Kasih Kemuliaan: pelayanan terhadap panti asuhan - riska azizah; Felix Setiawan Peranginangin; Solatiah Lintang; Haratua Aritonang; Weni Sapira Matondang; Rizki Ananda; Fajar Utama Ritonga (Pengelola Jurnal Politeknik Negeri Ketapang, 2023)
English Social Work Journal that social service is a form of social work practice that is embodied in social service agencies. This is in line with the change in mindset in the provision of social services. Efforts made by social care institutions for children are providing social services to neglected children who do not have parents, father, mother or family and are economically disadvantaged. To realize this, it is necessary to increase the professionalism of social services, one of which is to increase the quality of services in social institutions. This journal discusses the quality of social services at the Shade of Kasih Kemuliaan Orphanage. This was done by carrying out an English learning program where the training program was carried out at the Shade of Kasih Kemuliaan Orphanage and there were 13 children and 6 students involved. and fundraising to meet the basic needs of the Orphanage by providing groceries.